Extracellular vesicles in chronic kidney disease: diagnostic and therapeutic roles - Zheng, Yixuan; Wang, Hui; Li, Xueying; Xie, Jing; Fan, Junming; Ren, Sichong (Frontiers in Pharmacology, 2024)
Chronic kidney disease (CKD) is a progressive disorder characterized by structural and functional changes in the kidneys, providing a global health challenge with significant impacts on mortality rates. Extracellular vesicles (EVs), are vital in the physiological and pathological processes associated with CKD. They have been shown to modulate key pathways involved in renal injury, including inflammation, fibrosis, apoptosis, and oxidative stress. Currently, the application research of EVs in the diagnosis and treatment of CKD is highly prevalent. However, there is currently a lack of standardized guidelines for their application, and various methodologies have advantages and limitations. Consequently, we present an comprehensive summary elucidating the multifaceted involvement of EVs in both physiological and pathological aspects in CKD. Furthermore, we explore their potential as biomarkers and diverse therapeutic roles in CKD. This review provides an overview of the current state of research on application of EVs in the diagnosis and therapeutic management of CKD.